Optimism and Hope: The Psychological Foundation for Building Grit in Islamic Boarding School Students - Putra, Rahman Pranovri; Sudirman, Subhan Ajrin; Yusri, Nur Aisyiah; Ramadhanti, Auliya (Journal of Psychological Perspective, 2025)
The high dropout rate in Islamic boarding schools in Indonesia poses a significant educational challenge. Many adolescents lose interest in continuing their education at boarding schools, resulting in many of them dropping out. Increased grit is believed to have a significant impact on the academic success of adolescents in these schools. This study examines the influence of optimism and hope on grit in adolescents attending Islamic boarding schools. The study uses a quantitative ex-post facto approach, involving 367 teenagers selected through multistage random sampling. Data were collected using the Short Grit Scale (Grit-S), an optimism scale, and the Dispositional Adult Hope Scale, and analyzed using multiple regression with SPSS Version 27. The results showed that optimism and hope together have a positive and significant effect on grit (p 0.05). Partially, optimism acts as a positive belief in future outcomes that encourages students to view challenges as opportunities, while hope provides clarity of purpose and the ability to devise alternative strategies to overcome obstacles. These findings confirm that the synergy between optimism and hope forms a psychological foundation that strengthens students' resilience amid academic and spiritual demands in the dormitory.